Proceedings of the 2015 ASPEN Research Workshop—Taste Signaling: Impact on Food Selection, Intake, and Health. (23rd November 2015) - Spector, Alan C.; le Roux, Carel W.; Munger, Steven D.; Travers, Susan P.; Sclafani, Anthony; Mennella, Julie A.
Abstract : This article summarizes research findings from 6 experts in the field of taste and feeding that were presented at the 2015 American Society for Parenteral and Enteral Nutrition Research Workshop. The theme was focused on the interaction of taste signals with those of a postingestive origin and how this contributes to regulation of food intake through both physiological and learning processes. Gastric bypass results in exceptional loss of fat mass and increases in circulating levels of key gut peptides, some of which are also expressed along with their cognate receptors in taste buds. Changes in taste preference and food selection in both bariatric surgery patients and rodent models have been reported. Accordingly, the effects of this surgery on taste‐related behavior were examined. The conservation of receptor and peptide signaling mechanisms in gustatory and extraoral tissues was discussed in the context of taste responsiveness and the regulation of metabolism. New findings detailing the features of neural circuits between the caudal nucleus of the solitary tract (NST), receiving visceral input from the vagus nerve, and the rostral NST, receiving taste input, were discussed, as was how early life experience with taste stimuli and learned associations between flavor and postoral consequences of nutrients can exert potent and long‐lasting effects on feeding.